Improving the Hanging Ala - Yap, Eduarda (Facial Plastic Surgery, 2012)
The hanging ala can be lifted via removal of a piece of triangular vestibular skin shaped like a sail; the alar rim skin is rolled and sutured into the defect to form a new lifted rim margin.
Keywords: sail; vestibular groove; alar rim